2020
DOI: 10.19087/imv.2020.9.4.512
|View full text |Cite
|
Sign up to set email alerts
|

Pendugaan Bobot Karkas Sapi Bali Jantan dan Betina Berdasarkan Panjang Badan dan Lingkar Dada

Abstract: Bobot karkas adalah bobot ternak yang sudah disembelih, dikuliti, dan telah dipisahkan bagian kepala, jeroan, keempat kaki mulai dari persedian carpus atau tarsus ke bawah. Jumlah sampel yang diambil yaitu 20 sapi jantan dan 24 sapi betina. Panjang tubuh diukur dari bongkol bahu (tuberositas humeri) sampai ujung tulang duduk (tuber ischii) menggunakan roll meter dan untuk lingkar dada diukur dengan melingkarkan pita ukur pada bagian dada belakang bahu. Karkas yang sebelumnya sudah dikurangi bagian kepala, kuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Furthermore, male livestock produce testosterone, an androgen steroid hormone that regulates growth and is produced by interstitial cells and adrenal glands. This hormone can increase the metabolic rate in the body, resulting in faster growth compared to female livestock [21]. These factors may explain the observed differences in body weight and weight gain between male and female thin-tailed sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, male livestock produce testosterone, an androgen steroid hormone that regulates growth and is produced by interstitial cells and adrenal glands. This hormone can increase the metabolic rate in the body, resulting in faster growth compared to female livestock [21]. These factors may explain the observed differences in body weight and weight gain between male and female thin-tailed sheep.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be influenced by genetic factors, sex, and hormones. Ananda et al [21] suggested that increasing the size of male livestock results in androgen hormones that stimulate growth. These androgen hormones can activate the production of anabolic proteins, leading to increased growth in male livestock and resulting in larger body size compared to female livestock [22].…”
Section: Discussionmentioning
confidence: 99%
“…Super male chickens are taller than super female chickens (Putri et al, 2020); likewise, in Merawang males, it is higher than in female Merawang chickens (Sari et al, 2021). The difference in the average body sizes of male KUB chickens and female KUB is thought to be influenced by the hormone testosterone, which can stimulate increased expenditure of other hormones as growth boosters so that male livestock can be superior to female livestock (Ananda et al, 2020). This condition causes the body size of male KUB chickens to be higher than female KUB chickens.…”
Section: Average Body Sizesmentioning
confidence: 99%
“…Menurut (Sugiantoro, 2015) menyampaikan tentang koleksi museum Sonobudoyo Yogyakarta dengan menggunakan visual 3D lebih memudahkan pengunjung untuk memahami barang peninggalan di musem tanpa harus bersentuhan langsung dengan barang koleksi secara fisik. Serta dalam (Ananda et al, 2020) dan (Song et al, 2018) penelitian tentang pengukuran badan sapi secara otomatis dengan kamera 3D juga lebih efisien tanpa harus bersentuhan langsung. (Huang & Huang, 2022) Ditambahkan juga berdasarkan penelitian (Ilyasa et al, 2020) dan (Purwanto et al, 2015) tentang sistem pengukuran baju untuk menentukan ukuran baju dengan kamera kinect menggunakan LZW dan CLHE disampaikan bahwa ada ketidaksesuaian 18% karena menggunakan kamera kinect dari penjual.…”
Section: Pendahuluanunclassified